Pengembangan Video Pembelajaran Podcast Makanan Fusion - Laily, Setiani Nur; Kandriasari, Annis; Cahyana, Cucu (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to develop and test the feasibility of a learning medium in the form of a fusion food video podcast to support the Culinary Skills Concentration subject, specifically the Indonesian Cake and Pastry Products element, for eleventh-grade students in the Culinary Skills Program. Based on the questionnaire results, the Indonesian Cake and Pastry Products element is the one that most requires the development of learning media. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The data analysis technique in this research and development study is descriptive qualitative. The trial was conducted at SMK Negeri 28 Jakarta. The trials conducted include one-to-one testing with 3 respondents, small group testing with 9 respondents, and field group testing with 30 respondents. This learning medium has been validated by experts with a score of 93% for the material aspect, 87% for the media aspect, and 86% for the language aspect. The results of the one-to-one test were 95%, the small group test 95%, and the field group test 97%. Based on the test results, it can be concluded that the development of this fusion food video podcast is considered effective in helping students understand the material in an interesting and easily comprehensible way.